Assessment of BRAF-V600E, KRAS, NRAS and EGFR mutations in papillary thyroid carcinoma and Hashimoto’s thyroiditis - Ilkay Ozdamar, Osman; Ozbilen Acar, Gul; Ozen, Filiz; Zenginkinet, Tulay (ENT Updates, 2020)
Objective: The present study compared three study groups composed of patients with only papillary thyroid carcinoma (PTC), patients with only Hashimoto’s thyroiditis (HT) and patients with PTC+HT in terms of BRAF-V600E, KRAS, NRAS and epidermal growth factor receptor (EGFR) mutations. Also, the association between clinicopathological prognostic indicators including tumor multifocality, extrathyroidal extension (ETE), lymph node (LN) metastasis and recurrence and BRAF-V600E mutations were investigated in the PTC and PTC+HT groups. Methods: A total of 53 patients (two males and 51 females) who underwent a hemi/total thyroidectomy due to suspicion of malignancy or malignant lesion according to the thyroid cytopathology participated in the study. The study groups were composed of 19 patients with PTC, 18 with PTC+HT and 16 with HT according to the histopathological examination records. Histopathological sections from the paraffin blocks of the patients were investigated for BRAF-V600E, KRAS, NRAS and EGFR gene mutations using real-time polymerase chain reaction (PCR) assay. Results: There was no significant difference between the groups in terms of BRAF-V600E KRAS, NRAS and EGFR mutation rates. Also, presence of the BRAF-V600E mutation was not correlated with the prognostic indicators for the patients with PTC and PTC+HT. Conclusion: In the present study, no significant association was found between PTC and HT, and the BRAFV600E, KRAS, NRAS and EGFR mutations. Further studies with a larger number of patients may help to clarify the clinicopathological and diagnostic importance of the BRAF-V600E, KRAS, NRAS and EGFR mutations in thyroid diseases.